Analisis komparatif kepuasan konsumen pada variabel, produk dan harga terhadap produk pengankutan merek mitshubisi t120ss dan suzuky carry di samarinda - Methodius Ardiyanto; J. Kuleh; Asnawati Asnawati (Faculty of Economics and Business Mulawarman University, 2016)
Aimed of research it to know the existence of consumer’s satisfaction differences buyer at the same time using Suzuki Carry and Mitsubishi Colt based on service, product and price. From the result of data analysis and calculation were obtained the result of t-test of consumer’s satisfaction buyer at the same time using Suzuki Carry and Mitsubishi Colt. If both of them are analyzed based on service, product and price, the result of the analysis equal to 3,378 and 3,403. While based are seen based on service, the t-test value is -3,017 and based on product,the value is 4,194 and also based on price t-test value is -1,192. From the result of research obtained that there are differences of consummer’s satisfaction using Suzuki Carry and Mitsubishi Colt based on product and service. Whereas, based on price variable, there’s not differences of consumer’s satisfaction. On the whole, from costumer’s satisfaction buyer at the same time using Suzuki Carry and Mitsubishi Colt, and after all of the observed what we had done,the conclusion of the hypotesis what we made is denied.Keyword: Research Obtained that There are Differences of Consummer’s